Transforming Human Capital Management: The Complexity Paradigm and Post-conventional Management (Gestión y Gerencia, 2025)
The complexity paradigm acknowledges that organizations are composed of multiple interactions and relationships among individuals, processes, and structures. Conversely, Post-conventional Management aims to foster greater humanism within organizations by providing a culture more focused on employees. Within this context, Human Capital Management (HCM) is undergoing a significant transformation, particularly in its approach to addressing organizational complexity. Employing a qualitative approach, through a content analysis applied to a literature review of three dozen selected texts, based on the definition of keywords such as "Organizational complexity," "Post-conventional management," and "Human resource management," a growing trend towards adopting more holistic and humanistic approaches in people management was identified. The findings reveal that integrating these paradigms promotes an organizational culture that values adaptability, collaboration, and continuous learning. The study demonstrated that organizational complexity necessitates an HCM that recognizes the interconnectedness among the different components of the organization. Post-conventional management, for its part, emphasizes the importance of the integral development of employees and their active participation in decision-making. By combining these approaches, organizations can foster innovation, enhance employee engagement, and increase their capacity to adapt to environmental changes. However, implementing these paradigms presents challenges, such as the need to develop new tools for measuring and evaluating performance, as well as resistance to change.
Keywords: Complexity dynamics; Human resources management; Personnel development; Post-conventional management; Organizational change.